Performance Evaluation of CTP Routing Protocol for Mobile Wireless Sensor Network - Mohd Nazim, Jambli; A.M., Farha Anati; Halikul, Lenando; Johari, Abdullah; M.S, Sinarwati (IEEE, 2013)
Recently, extensive research has been conducted on Wireless Sensor Network (WSNs) due to their wide range of potential applications ranging from environmental monitoring to critical military surveillance. Most of these applications can be deployed either in static or mobile environment. In static WSN, the change of sensor nodes’ topology is normally caused by node failure which is due to energy depletion. However, in mobile WSN (MWSN), the main reason of the topology change is caused by the node movement. Since the sensor nodes are limited in power supply and have a low radio frequency coverage, they are easily losing their connection with neighbours and difficulties to transmit their packets towards sink node. The reconnection process from one node to another node consumes more energy that related to control packets. Using Collection Tree Protocol (CTP) routing protocol in MWSN application shows degradation in network performance due to high speed of mobile nodes. In this paper, through extensive simulation we evaluated the capability of CTP on how far it can react to network topology change in MWSN. We investigated the performance metrics namely data delivery ratio (DDR) and energy consumption of mobile nodes with various speed. Our performance study demonstrates that by applying the existing CTP in MWSN, the results show a low percentage of data delivery ratio and higher total network energy consumption in high speed of mobile nodes due to serious broken link and frequent tree re-generation caused by nodes movement. We also identify factors that contribute to the degradation of CTP’s performance and highlight some key research problems that need to be addressed for successful implementation of CTP in MWSN.